RNA-Seq analysis during the life cycle of Cryptosporidium parvum reveals significant differential gene expression between proliferating stages in the intestine and infectious sporozoites. Issue 6 (May 2018) - Lippuner, Christoph; Ramakrishnan, Chandra; Basso, Walter U.; Schmid, Marc W.; Okoniewski, Michal; Smith, Nicholas C.; Hässig, Michael; Deplazes, Peter; Hehl, Adrian B.
Graphical abstract: Highlights: Sporozoite versus intracellular Cryptosporidium parvum gene expression was studied. RNA-Seq revealed C. parvum genes that are expressed in a stage-specific manner. 173 genes (26 for predicted secreted proteins) were upregulated in sporozoites. 1259 genes were upregulated in intracellular stages. Our results allow identification of drug and vaccine targets against C. parvum . Abstract: Cryptosporidium parvum is a major cause of diarrhoea in humans and animals. There are no vaccines and few drugs available to control C. parvum . In this study, we used RNA-Seq to compare gene expression in sporozoites and intracellular stages of C. parvum to identify genes likely to be important for successful completion of the parasite's life cycle and, thereby, possible targets for drugs or vaccines. We identified 3774 protein-encoding transcripts in C. parvum. Applying a stringent cut-off of eight fold for determination of differential expression, we identified 173 genes (26 coding for predicted secreted proteins) upregulated in sporozoites. On the other hand, expression of 1259 genes was upregulated in intestinal stages (merozoites/gamonts) with a gene ontology enrichment for 63 biological processes and upregulation of 117 genes in 23 metabolic pathways. There was no clear stage specificity of expression of AP2-domain containing transcription factors, although sporozoites had a relatively small repertoire of these important regulators. Our RNA-Seq analysis revealed a new calcium-dependent protein kinase, bringing the total number of known calcium-dependent protein kinases (CDPKs) in C. parvum to 11. One of these, CDPK1, was expressed in all stages, strengthening the notion that it is a valid drug target. By comparing parasites grown in vivo (which produce bona fide thick-walled oocysts) and in vitro (which are arrested in sexual development prior to oocyst generation) we were able to confirm that genes encoding oocyst wall proteins are expressed in gametocytes and that the proteins are stockpiled rather than generated de novo in zygotes. RNA-Seq analysis of C. parvum revealed genes expressed in a stage-specific manner and others whose expression is required at all stages of development. The functional significance of these can now be addressed through recent advances in transgenics for C. parvum, and may lead to the identification of viable drug and vaccine targets.